FLAMSA reduced‐intensity conditioning is equally effective in AML patients with primary induction failure as well as in first or second complete remission. (25th August 2015) - Holtick, Udo; Shimabukuro‐Vornhagen, Alexander; Chakupurakal, Geothy; Theurich, Sebastian; Leitzke, Silke; Burst, Anke; Hallek, Michael; von Bergwelt‐Baildon, Michael; Scheid, Christof; Chemnitz, Jens M.
Abstract: Reduced‐intensity conditioning regimens have demonstrated lower toxicity but increased relapse rates in the context of allogeneic hematopoietic stem cell transplantation (aSCT) for patients with acute myelogenous leukemia (AML). The FLAMSA‐ reduced‐intensity conditioning (RIC) regimen, combining a cytoreductive and a transplant‐conditioning part, has been described to be efficacious in patients with refractory disease. We retrospectively analyzed clinical data of 130 patients with AML after aSCT following FLAMSA RIC at our center. The median follow‐up was 37 (10–125) months. The 4‐yr overall and disease‐free survival rates of the whole cohort were 45% and 40%. Cumulative incidence of relapse was 29%, 35%, and 40% at 1, 2, and 4 yr. There were no significant differences regarding overall and disease‐free survival for patients transplanted in CR1, CR2, or primary induction failure (PIF). Patients with refractory disease after salvage therapy had significantly lower disease‐free and overall survival (OS). Disease‐free and OS rates were also significantly decreased in patients with 10% or more BLASTS at transplant. non‐relapse mortality was 15%, 19%, and 20% at 1, 2, and 4 yr and similar in all cohorts. These data underscore the potency of the FLAMSA RIC regimen for patients with AML especially with PIF. The decision for re‐induction therapy prior to aSCT in relapsed patients has to be weighed against the potential toxicity of this approach and might be influenced by the amount of leukemic BLASTS present. Only randomised trials will answer this important question.